Exploring factors reflecting Chinese students’ study abroad destination choice: A case study of Chinese students in Japan - Jiao, Ran (Journal of International Students, 2025)
Japan has become the most popular study destination among non-English-speaking countries in Asia. Within the broader literature on students’ personal motivation and parental influence, this study examines how Chinese students construct motivational factors when Japan is chosen as their study destination. In this study, 17 participants at a Japanese university were interviewed via semistructured interviews to collect data. This study employed a three-stage qualitative data analysis process: raw data coding, data categorization, and thematic development. The findings revealed that the push factors identified by the participants included cultural, educational and career development aspects. The pull factors encompass social factors such as a stable society and convenient lifestyle in Japan, as well as natural environmental features, including beautiful landscapes and scenic views. The study concludes that both push and pull factors play significant roles in motivating Chinese students’ desire to study in Japan.